2006
DOI: 10.1007/s10865-006-9057-4
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Age, and Immune Function: Toward a Lifespan Approach

Abstract: Both aging processes and psychological stress affect the immune system: Each can dysregulate immune function with a potentially substantial impact on physical health. Worse, the effects of stress and age are interactive. Psychological stress can both mimic and exacerbate the effects of aging, with older adults often showing greater immunological impairment to stress than younger adults. In addition, stressful experiences very early in life can alter the responsiveness of the nervous system and immune system. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
198
0
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(215 citation statements)
references
References 120 publications
(132 reference statements)
11
198
0
6
Order By: Relevance
“…32,33 In one such study, chronically stressed men and women caring for spouses with dementia showed a four-fold increase in interleukin-6 production compared with noncare partners. Those with the greatest interleukin-6 levels had a two-fold increased risk of death in the next 4 to 5 years compared with those with the lowest levels.…”
Section: Care Partner Socioeconomic Burdenmentioning
confidence: 99%
“…32,33 In one such study, chronically stressed men and women caring for spouses with dementia showed a four-fold increase in interleukin-6 production compared with noncare partners. Those with the greatest interleukin-6 levels had a two-fold increased risk of death in the next 4 to 5 years compared with those with the lowest levels.…”
Section: Care Partner Socioeconomic Burdenmentioning
confidence: 99%
“…The way ageing and stress simultaneously act to affect the immune response seems to be influenced not only by the way organisms age, but it could be highly influenced also by early life event experience (Graham et al 2006). Long-term effects seem to emerge not only after negative maternal behaviours, such as poor prenatal nutrition, but also following external, psychological and environmental stress in mothers (reviewed in Graham et al 2006).…”
Section: Ageing Stress and The Immune Systemmentioning
confidence: 99%
“…Finally, previous research has shown that older adults and stressed persons have parallel changes in an overall decline in health (Graham, Christian, & Kiecolt-Glaser, 2006).…”
Section: Stress Across the Lifespanmentioning
confidence: 83%
“…Also consistent with previous research, older adults experience stress over their general decline in health (Aldwin, 2007). This may result from older adults who experience an increased risk for life-threatening illness (Castle, 2000;Graham et al, 2006). Further, there are parallel changes that older adults have with stressed individuals, such as immune dysregulation (Graham et al, 2006).…”
Section: Stress Across the Lifespanmentioning
confidence: 99%
See 1 more Smart Citation